2021
DOI: 10.1177/19458924211026416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urban Particulate Matter on the Olfactory System in a Mouse Model

Abstract: Background Exposure to urban particulate matter (UPM) is linked to the aggravation of various health problems. Although the nasal cavity is the first barrier to encounter UPM, there is a lack of studies on the impact of UPM on the olfactory area. The purpose of this study was to investigate the cytotoxic effects of UPM on mouse olfactory epithelium, the underlying pathophysiology involved, and changes in cytokine levels. Methods Mice were divided into 4 groups: control, 400UPM (administered 400 µg UPM daily; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Their expression in tissues other than olfactory epithelial cells has been extensively studied and increasingly reported. 7,8 Olfactory receptor 78 (Olfr78), as a member of GPCRs, has been identified the mainly receptor for Short-chain fatty acids (SCFAs), 9 which is widely expressed, such as in the brain tissues, 10 kidneys, 11 arterioles, 12 carotid bodies, 13 macrophages, 14 colon, 15 and prostate. 16 Early reports showed that SCFAs inhibit vascular calcification by regulating the osteogenic reprogramming of vascular smooth muscle cells, thereby alleviating chronic kidney injury and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their expression in tissues other than olfactory epithelial cells has been extensively studied and increasingly reported. 7,8 Olfactory receptor 78 (Olfr78), as a member of GPCRs, has been identified the mainly receptor for Short-chain fatty acids (SCFAs), 9 which is widely expressed, such as in the brain tissues, 10 kidneys, 11 arterioles, 12 carotid bodies, 13 macrophages, 14 colon, 15 and prostate. 16 Early reports showed that SCFAs inhibit vascular calcification by regulating the osteogenic reprogramming of vascular smooth muscle cells, thereby alleviating chronic kidney injury and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Odour receptors (OR) constitute a superfamily of G protein coupled receptors (GPCRs). Their expression in tissues other than olfactory epithelial cells has been extensively studied and increasingly reported 7,8 . Olfactory receptor 78 (Olfr78), as a member of GPCRs, has been identified the mainly receptor for Short‐chain fatty acids (SCFAs), 9 which is widely expressed, such as in the brain tissues, 10 kidneys, 11 arterioles, 12 carotid bodies, 13 macrophages, 14 colon, 15 and prostate 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Roxbury et al, examine how chemosensory dysfunction affects nutrition and diet in US Adults 19 , and Kim et al, examine how urban particulate matter, increasing as pollution continues to increase in densely populated urban areas and as wildfires have affected air quality nationwide, affect the olfactory system. 20 With the myriad trials and tribulations of the past 2 years, it is easy to ignore not only the progress we have made, but the advancements yet to come. I look forward to our readers taking a moment to pause and read not just AJRA, but the numerous academic publications which we are so lucky to have, and find a moment of separation from the hectic nature of our daily lives.…”
mentioning
confidence: 99%